Incidence of hermaphrodite in green mussel Perna viridis along the west coast of Peninsular Malaysia - Al-Barwani, Said Mohammed Hilal; Arshad, Aziz; Sarker, S. M. Nurul Amin Harmuj Ali; Bujang, Japar Sidik (Academic Journals, 2013)
Incidences of hermaphroditism in green mussels (Perna viridis) were determined in four different areas (Sebatu, Port Dickson, Muar and Johor Bahru) along the west coast of Peninsular Malaysia. In Sebatu, 1000 specimens of green mussels were used for the visual determination of sex ratios. The male:female visual ratio was 1:0.79. Three hundred and seventeen individuals were also sexually identified using histology technique. Male to female ratio was 1:1.01. Two hermaphrodite specimens were recorded during the months of June and September, 2004. In Port Dickson, 319 specimens were visually sex-determined, the male: female ratio was 1.00:0.86. One hundred forty one were also histologically identified. Male: female ratio was 1.00:0.96. There was no hermaphrodite specimen encountered in this population. For the population of Muar and Johor Bahru, the entire specimen’s numbers were visually sex-determined first and later confirmed by histological procedure. The male:female ratio was 0.72:1.00 and 1.00:0.95. No hermaphrodite specimen was found at either site. The pooled samples from different months showed no significant seasonal deviation in the sex ratio from a 1:1 ratio (Chi-square test, p>0.05).